Afterword: Witness to the archive. Issue 1 (2nd January 2022) - Arabindan-Kesson, Anna
ABSTRACT: This afterword uses the work of artist Patricia Kaersenhout and Black feminist scholars to reflect on the implications of working with colonial archives and their forms of erasure.